Influence of age and scholing on the performance in a modified Mini-Mental State Examination version: a study in Brazil Northeast Influência da idade e escolaridade sobre a performance da versão modificada do Mini-Exame do Estado Mental: estudo no nordeste do Brasil - Paulo Roberto de Brito-Marques; José Eulálio Cabral-Filho (Arquivos de Neuro-Psiquiatria)
Performance in cognitive tests can be influenced by age and education level. In developing countries, formal education is limited for most people. Application of the Mini-Mental State Examination (MMSE) test, in its original version could have an adverse effect on the evaluation of low educated and elderly individuals. OBJECTIVE: To assess the cognitive performance of low and middle educated old people in a modified version of the adapted to portuguese language MMSE. METHOD: A study was carried out enrolling 253 individuals, aged 60 to 90 years included in different schooling levels. Four educational groups were studied: illiterate;1-4 schooling years; 5-8 schooling years and over 8 schooling years. Besides, the sample was also studied according to six classes: 60-65, 66-70, 71-75, 76-80, 81-85 and 86-90 years. The modified version (mo-MMSE) included modifications in copy and calculation items from the adapted MMSE (ad-MMSE) to Portuguese language. The maximum possible score was the same in the two versions: total, 30; copy, 1 and calculation, 5. RESULTS: mo-MMSE scores were significantly higher than ad-MMSE for every age classes. A negative correlation was observed between age and scores in individuals of 1-4 and in individuals over eight schooling years, both in ad-MMSE and mo-MMSE. However, there was not a significant correlation between age and scores in illiterate group and in individuals of 5-8 schooling years. CONCLUSION: The modification of copy and calculation items of ad-MMSE, are responsible by the best performance in mo-MMSE. Cultural background could have influenced this result. Individuals with more than eight years of formal instruction are protected against a reduction of their capacity to solve cognitive tests. However, low instructed individuals have not this capacity and so they present signals of intellectual aging before they become elderly people. A realização de testes cognitivos pode ser influenciada por fatores como idade e educação. Nos países em desenvolvimento, a educação formal está limitada para a maioria da população. A aplicação do teste Mini-Exame do Estado Mental (MEEM), na sua versão original, pode ter efeito adverso em pessoas com baixo nível de educação e idosos. OBJETIVO: Avaliar a performance cognitiva da população de baixo e médio nível de educação e idosa em uma versão modificada do MEEM adaptado para língua portuguesa. MÉTODO: Foram estudados 253 indivíduos idosos com idades entre 60 e 90 anos incluídos em diferentes níveis de escolaridade. O estudo foi constituído por quatro grupos de escolaridade: analfabeto; 1-4 anos; 5-8 anos e mais de 8 anos. A amostra também foi estudada de acordo com seis classes: 60-65, 66-70, 71-75, 76-80, 81-85 e 86-90 anos. A versão modificada (MEEM-mo) incluiu modificações nos itens de cópia e cálculo da versão adaptada (MEEM-ad) para a língua portuguesa. O escore máximo foi o mesmo para ambas as versões: total, 30; cópia, 1 e cálculo, 5. RESULTADOS: O escore do MEEM-mo foi mais significativo do que o do MEEM-ad para cada classe de idade. Uma correlação negativa foi observada entre a idade e o escore em indivíduos de 1-4 anos e em indivíduos com mais de oito anos de escolaridade, ambas no MEEM-ad e MEEM-mo. Não existia correlação significante entre idade e escore no grupo de analfabetos e nos indivíduos de 5-8 anos de escolaridade. CONCLUSÃO: As modificações realizadas nos itens cópia e cálculo do MEEM-ad são responsáveis pela melhor performance encontrada no MEEM-mo. Os fatores culturais podem ter influenciado este resultado. Indivíduos com mais de oito anos de instrução formal são protegidos contra uma redução de suas capacidades para solucionar testes cognitivos. Entretanto, indivíduos com baixo nível de instrução não têm esta capacidade e, dessa forma, apresentam sinais de envelhecimento antes de se tornarem pessoas idosas.